2002
DOI: 10.1152/ajpcell.2002.282.1.c213
|View full text |Cite
|
Sign up to set email alerts
|

Voxx: a PC-based, near real-time volume rendering system for biological microscopy

Abstract: Confocal and two-photon fluorescence microscopy have advanced the exploration of complex, three-dimensional biological structures at submicron resolution. We have developed a voxel-based three-dimensional (3-D) imaging program (Voxx) capable of near real-time rendering that runs on inexpensive personal computers. This low-cost interactive 3-D imaging system provides a powerful tool for analyzing complex structures in cells and tissues and encourages a more thorough exploration of complex biological image data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 4 publications
(3 reference statements)
1
97
0
Order By: Relevance
“…Images were obtained using a Zeiss Pascal confocal microscope. Voxx rendering software (Clendenon et al, 2002) was used for 3D reconstruction. LacZ expression in whole mounts of TS muscles from heterozygous tenascin-C-null mutant mice was detected by X-gal staining solution, with a solution containing 2 mM MgCl 2 , 5 mM K 3 Fe(CN) 6 , 5 mM 0.02% NP-40 and 1 mg/ml X-gal (5-bromo-4-chloro-3-indolyl-D-galactoside; Sigma).…”
Section: Immunocytochemistry and Histochemistrymentioning
confidence: 99%
“…Images were obtained using a Zeiss Pascal confocal microscope. Voxx rendering software (Clendenon et al, 2002) was used for 3D reconstruction. LacZ expression in whole mounts of TS muscles from heterozygous tenascin-C-null mutant mice was detected by X-gal staining solution, with a solution containing 2 mM MgCl 2 , 5 mM K 3 Fe(CN) 6 , 5 mM 0.02% NP-40 and 1 mg/ml X-gal (5-bromo-4-chloro-3-indolyl-D-galactoside; Sigma).…”
Section: Immunocytochemistry and Histochemistrymentioning
confidence: 99%
“…Montages were assembled and annotated using Photoshop (Adobe, Mountain View, CA). Volume renderings were conducted using Voxx, a PC-based image analysis program developed at the Indiana Center for Biological Microscopy (Clendenon et al, 2002) and available at no charge (http://nephrology.iupui.edu/imaging/voxx).…”
Section: Image Processing For Presentationmentioning
confidence: 99%
“…A series of optical section comprising the complete volume of the tectal arborization was collected, and these images were rendered to create a three-dimensional volume that could be viewed at any orientation using voxel rendering software, Voxx (Clendenon et al, 2002). Inspection of these volumes showed that control retinotectal arborizations were extensive and finely branched ( Fig.…”
Section: Defective Retinotectal Projection In Cdh4 Knockdown Embryosmentioning
confidence: 99%